STRATEGI MURAKAMI HARUKI DALAM MERAIH POSISI DAN LEGITIMASI DI ARENA SASTRA JEPANG - , Santi Andayani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Murakami Haruki not only a novelist, he is also known as a translator. His works are both fiction and nonfiction got apreciation and recognition like national and international prizes. By his sucsess, Murakami became one of writers who could prove that the profession of writer can make a financial advantage, popularity and prestige in social space. Eventhough he got all of those, he still doesnât got fully recognition from Japanese literary world. Literary elits consider his works did not represent the aesthetics of Japanese literary so that his works can not be categorized as high literature. These are the backgrounds of this research The purposes of this research are: first, in order to know the the condition of the field of power and the field of literary in Japan where his works are made. Second, to know the strategy of Murakami to fix his position in the field of literature. Third, to know the representation of Murakami Haruki regard to the field of power and the scheme of generative habitous which expressed in the novel of Noruwei no Mori. To solve the problems, the writer used theory of Pierre Bourdieu about the field of cultural production to analize the field of Japanese power and literary, the accumulation of capitals, and his strategy to obtain position and legitimation. The result of this research shows that the position of Murakami in social space does not stand at otonomous pole nor heterenomous pole. He stands at intersection of those poles. Those are Murakami does not obey the law that applied on the autonomous pole which representated by elit literary. On the other side, Murakami does not stand on the heteronomous pole because he does not follow the domination of media and publishers fully. Murakami uses the symbolic strategy to maintain or to improve the social acknowledgement as well as his strategy of reproduction to maintain or to increase capitals for the future. And he also uses strategy of reconvertion for his movement in social space because of his position among the dominant and the dominated position